Determinants of Job Performance among Medical Rehabilitation Health Personnel at Dr. Moewardi Hospital, Surakarta, Central Java: A Path Analysis Evidence - Sisybania Sisybania; Mahendra Wijaya; Bhisma Murti (Journal of Health Policy and Management, 2021)
Background: The quality of a health institution is determined by human resources (HR) and the quality of staff services. The quality of health human resources is measured by employee performance and productivity especially services that are directly related to patients, such as the Department of Medical Rehabilitation. This study aimed to analyze the psychosocial economic determinants of the performance of medical rehabilitation health personnel.Subjects and Method: This study used a cross-sectional method. This study was conducted from May 2020 to June 2020. The sample was selected by exhaustive sampling by 200 medical rehabilitation health personnel at Dr. Moewardi, Surakarta. The dependent variable was performance. The independent variables were motivation, skill, work atmosphere, facilities and infrastructure, work experience, training, education, leadership style, incentive, reinforcement, vicarious learning, and observational learning. The data were collected using questionnaires and analyzed using path analysis with STATA version 13.Results: Medical rehabilitation health personnel had a likelihood of performing well with participative leaders (b=2.24; 95%CI=0.09 to 1.44; p=0.025), sufficient incentives (b=3.19; 95%CI=0.42 to 1.76; p<0.001), high motivation (b=3.38; 95%CI=0.51 to 1.93; p<0.001), by attenting training and education for medical rehabilitation (b=1.86; 95%CI=-0.03 to 1.27; p=0.064), good reinforcement (b=1.72; 95%CI=- 0.09 to 1.42; p=0.086), training and education through incentives (b=1.86; 95%CI=- 0.02 to 1.11; p=0.062), conducive work atmosphere through motivation (b=2.49; 95%CI=0.16 to 1.42; p=0.013).Conclusion: The performance of medical rehabilitation health personnel is affected by leadership style, incentives, motivation, training and education, work atmosphere, and reinforcement.Keywords: social cognitive, performance, path analysisCorrespondence: Sisybania, Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami No.36 A, Surakarta, Indonesia. Email: sisybania@gmail.com. Mobile: +6289676804589Journal of Health Policy and Management (2021), 01(01): 01-12https://doi.org/10.26911/thejhpm.2021.06.01.01.